Employment, growth and reforms in Jamaica - Alleyne, Dillon (ECLAC SantiagoCL, 2000)
Seeks to determine the ability of the Jamaican economy to generate productive employment, and how this has been affected by reforms implemented in the last 15 years. Focuses primarily on labour demand in the formal sector and the dynamics of salaried employment. Stresses, as well, the importance of the informal sector and supply dynamics (volume and compensation of labour).